2023
DOI: 10.1021/acs.oprd.2c00386
|View full text |Cite
|
Sign up to set email alerts
|

Development of Adagrasib’s Commercial Manufacturing Route

Abstract: A commercial route to adagrasib (1) was developed to support clinical and commercial needs. Yield was improved to 32% over six chemical steps. A doubly regioselective SNAr reduced consumption of a chiral intermediate, reaction optimization led to parts per million palladium catalysis, and a new method to deprotect Cbz-groups were developed to mitigate risk associated with benzyl iodide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…( S )-Mandelic acid was identified as an optical resolution candidate based on structural similarity to related molecules, and it worked quite successfully in this application (Figure ). Piperazine was recovered with high enantiopurity and recovery (48.2% recovery, 99.64:0.32 er ( S : R )).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…( S )-Mandelic acid was identified as an optical resolution candidate based on structural similarity to related molecules, and it worked quite successfully in this application (Figure ). Piperazine was recovered with high enantiopurity and recovery (48.2% recovery, 99.64:0.32 er ( S : R )).…”
Section: Resultsmentioning
confidence: 99%
“…Adagrasib is an FDA-approved KRAS G12C inhibitor. The commercial and second-generation routes of manufacturing were recently disclosed. The piperazine building block is required at the metric ton scale, and accessing this fragment was unsatisfying in both cases (Figure , highlighted in blue).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the seminal report by Shokat et al a decade ago, it has been widely demonstrated that previously considered undruggable KRAS G12C mutations can now be targeted with high potency. In fact, several small molecules have been successfully developed as selective KRAS G12C inhibitors to treat cancer patients, including recently U.S. Food and Drug Administration (FDA) approved sotorasib and adagrasib as well as clinical candidates ARS-2102, JDQ443, and BI-0474 (Figure ). Genentech’s divarasib (GDC-6036, 1 ), a highly potent and selective small-molecule KRAS G12C covalent inhibitor, is currently being investigated in phase III clinical trials.…”
Section: Introductionmentioning
confidence: 99%